Duality of independence and interdependence: An adaptationist perspective. Issue 4 (October 2016) - Hashimoto, Hirofumi; Yamagishi, Toshio
Abstract : We propose a new framework for understanding cultural differences in self‐construal by noting the duality of this construct. Based on the analysis of the adaptive roles of self‐construal, we predicted that a US–Japan difference in self‐construal exists in the contrast between self‐expression and rejection avoidance. We confirmed these predictions using newly constructed self‐construal scales. Compared to Japanese respondents, American respondents were higher on self‐expression and lower on rejection avoidance. Our findings regarding the contrast between distinctiveness of the self and harmony seeking, which are traditionally discussed as the core features of independence and interdependence, did not support the standard cultural psychological view. The two groups of respondents did not differ on distinctiveness of the self and the American respondents were higher on harmony seeking than were Japanese respondents.